2010
DOI: 10.1016/s1836-9553(10)70021-7
|View full text |Cite
|
Sign up to set email alerts
|

Minimal difference between aerobic and progressive resistance exercise on metabolic profile and fitness in older adults with diabetes mellitus: a randomised trial

Abstract: NCT01000519.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 30 publications
2
29
1
Order By: Relevance
“…Overall, a total of 14 trials (16 reports) extracted from 9,477 articles met the eligibility requirements and were included for the present systematic review and meta-analysis [15][16][17][18][19][20][31][32][33][34][35][36][37][38][39][40]. One study was excluded since it was not described as randomised [41], and two trials provided no information on whether the AET was supervised [42,43].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, a total of 14 trials (16 reports) extracted from 9,477 articles met the eligibility requirements and were included for the present systematic review and meta-analysis [15][16][17][18][19][20][31][32][33][34][35][36][37][38][39][40]. One study was excluded since it was not described as randomised [41], and two trials provided no information on whether the AET was supervised [42,43].…”
Section: Resultsmentioning
confidence: 99%
“…Seven trials reported random sequence generation [16,31,32,[36][37][38][39], and only five trials reported allocation concealment [16,31,32,37,38]. None of the studies reported the blinding of volunteers towards the mode of intervention (ESM Fig.…”
Section: Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…The study group was undergone 50 minutes of aerobic training with a target heart rate of 65% of their age-predicted maximum heart rate [14].…”
Section: Intensity and Duration Of Trainingmentioning
confidence: 99%
“…Singaporeans of Asian origin ( AT/RT,-0.3% /-0.4%) showed a slightly superior effect from RT compared to AT [92]. Similar to South Asians, Singaporeans also have a higher percentage of body fat for the same body mass index as Caucasians [93].…”
Section: The Independent Effects Of At and Rt In Glycemic Control -Efmentioning
confidence: 99%